Meningkatkan Hasil Belajar Tari Dengan Menggunakan Media Audio Visual Di SMP Negeri 2 Bukittinggi - Oci Octavia; Fuji Astuti; Susmiarti Susmiarti (SENDRATASIK UNP, 2019)
This article aims to describe the use of audiovisual media in learning to improve the learning results of dance in SMP Negeri 2 Bukittinggi. This type of research is research action class (classroom action research) and measures planning (plan), persiapaan the implementation of the action, observation (observation), reflection (reflection). Research procedures can be divided into three stages: preparation, implementation, and completion. The research instrument was its own researchers and supporting instruments such as assisted with writing instruments, video cameras and photo cameras. And techniques in analyzing the data is carried out by means of direct data processing in the field. The results showed that the audio visual media can improve the learning results of dance students in learning the art of dance in the SMP Negeri 2 Bukittinggi. With the media can also attract the attention of students and reduce the saturation level of the students in the teaching and learning process. On cycle I results on tests of learning psychomotor cycle I IE 7 persons complete and the 25 people are not completely cognitive tests, while 18 people has been completed and 14 persons thoroughly, but not in cycle II has experienced an increase in psychomotor tests i.e. 30 people has been completed and 2 people don't completely, whereas in cognitive tests there were 26 people thoroughly and 6 people don't completely. The increase in the natural occurring due to use of audio visual media triggers and learning interest of students and coupled with planning that designed everything possible to improve the results of learning by doing evaluasai on each meeting.